Mathematical operation and symbol notation
 If given, 12 (169) 5, 4 (20) 2 and 1 (26) 5, then 7 (?) 3

View Hint View Answer Discuss in Forum
As, 12^{2} + 5 ^{2} ⇒ 144 + 25 = 169
4^{2} + 2^{2} ⇒ 16 + 4 = 20
and 1^{2} + 5^{2} ⇒ 1 + 25 = 26
Similarly,
7^{2} + 3^{2} = 49 + 9 = 58Correct Option: C
As, 12^{2} + 5 ^{2} ⇒ 144 + 25 = 169
4^{2} + 2^{2} ⇒ 16 + 4 = 20
and 1^{2} + 5^{2} ⇒ 1 + 25 = 26
Similarly,
7^{2} + 3^{2} = 49 + 9 = 58
 Select the correct combination of mathematical signs to replace * signs and to balance the given equation.
5 * 6 * 5 * 8 * 14

View Hint View Answer Discuss in Forum
Solve the equation by using option one by one.
5 * 6 * 5 * 8 * 14
From option (b),
After changing the symbol as per question,
5 x 6 ÷ 5 + 8 = 14
Apply the BODMAS Rule,
⇒ 5 x 6/5 + 8 = 14Correct Option: B
Solve the equation by using option one by one.
5 * 6 * 5 * 8 * 14
From option (b),
After changing the symbol as per question,
5 x 6 ÷ 5 + 8 = 14
Apply the BODMAS Rule,
⇒ 5 x 6/5 + 8 = 14
∴ 14 = 14
 If '' mean 'x', 'x' means '+', '+' means '÷' and '÷' means '', then
40 x 12 + 3  6 ÷ 60 = ?

View Hint View Answer Discuss in Forum
Given question is,
40 x 12 + 3  6 ÷ 60
According to the question, putting the real values of signs,
40 + 12 ÷ 3 x 6  60 = 40 + 4 x 6  60
Apply the BODMAS Rule
= 40 + 24  60 = 64  60 = 4Correct Option: D
Given question is,
40 x 12 + 3  6 ÷ 60
According to the question, putting the real values of signs,
40 + 12 ÷ 3 x 6  60 = 40 + 4 x 6  60
Apply the BODMAS Rule
= 40 + 24  60 = 64  60 = 4
 If '+' means '÷', 'x' means '+', '' means 'x' and '÷' means '', then which of the following equation is correct?

View Hint View Answer Discuss in Forum
Solve all option one by one,
36 + 6  3 x 2 = 20
After changing the symbol as per question,
36 ÷ 6 x 3 + 2 = 20
Apply the BODMAS rule,
⇒ 6 x 3 + 2 = 20Correct Option: B
Solve all option one by one,
36 + 6  3 x 2 = 20
After changing the symbol as per question,
36 ÷ 6 x 3 + 2 = 20
Apply the BODMAS rule,
⇒ 6 x 3 + 2 = 20
⇒ 18 + 2 = 20
⇒ 20 = 20
Direction: In these questions, relationship between different elements is shown in the statements. These statements are followed by two conclusions.
 Statements ::
D > B, C > K, K ≤ N, B < C, N < B
Conclusions ::
I. D > N
II. C ≥ K

View Hint View Answer Discuss in Forum
Conclusions
As per given question, we can draw the below conclusion,
I. D > N (✔)
II. C ≥ K (X)Correct Option: A
Conclusions
As per given question, we can draw the below conclusion,
I. D > N (✔)
II. C ≥ K (X)